B Cells in Patients With Melanoma: Implications for Treatment With Checkpoint Inhibitor Antibodies - Willsmore, Zena N.; Harris, Robert J.; Crescioli, Silvia; Hussein, Khuluud; Kakkassery, Helen; Thapa, Deepika; Cheung, Anthony; Chauhan, Jitesh; Bax, Heather J.; Chenoweth, Alicia; Laddach, Roman; Osborn, Gabriel; et al. (Frontiers in Immunology, 2021)
The contributions of the humoral immune response to melanoma are now widely recognised, with reports of positive prognostic value ascribed to tumour-infiltrating B cells (TIL-B) and increasing evidence of B cells as key predictors of patient response to treatment. There are disparate views as to the pro- and anti-tumour roles of B cells. B cells appear to play an integral role in forming tumour-associated tertiary lymphoid structures (TLS) which can further modulate T cell activation. Expressed antibodies may distinctly influence tumour regulation in the tumour microenvironment, with some isotypes associated with strong anti-tumour immune response and others with progressive disease. Recently, B cells have been evaluated in the context of cancer immunotherapy. Checkpoint inhibitors (CPI), targeting T cell effector functions, have revolutionised the management of melanoma for many patients, however, there remains a need to accurately predict treatment responders. Increasing evidence suggests that B cells may not be simple bystanders to CPI therapy. Mature and differentiated B cell phenotypes are key positive correlates of CPI response. Recent evidence also points to an enrichment in activatory B cell phenotypes and the contribution of B cells to TLS formation may facilitate induction of T cell phenotypes required for response to CPI. Contrastingly, specific B cell subsets often correlate with immune-related adverse events (irAEs) in CPI. With increased appreciation of the multifaceted role of B cell immunity, novel therapeutic strategies and biomarkers can be explored and translated into the clinic to optimise CPI therapy in melanoma.